TOSHIKO TAKENAKA / CHRISTOPH RADEMACHER / JAN KRAUSS / JOCHEN PAGENBERG / TILMAN MUELLER-STOY / CHRISTOF KARL: Patent Enforcement in the US, Germany and Japan - Dernauer, Marc (Zeitschrift für Japanisches Recht, 2019)
Oxford University Press, Oxford / New York 2015, lix, 450, 11 (Index) pp., £ 83, ISBN: 978-0-19-967920-1